The Oxymoron of Caged Animal Welfare: A Case Study in The Australian Caged Rabbit Meat Industry - Reem Lascelles (Universitat Autonoma de Barcelona. Facultat de Dret, 2019)
The objective of this research is to investigate how the current animal welfare regulatory approach in Australia is applied to domesticated rabbits with emphasis on rabbits used for meat. Australia’s animal welfare regime is critically examined by assessing the effectiveness of the Model Code of Practice for Animal Welfare: Intensive Husbandry of Rabbits (MCOPIHR) and the Five Freedoms in practice and what they mean to the actual wellbeing of rabbits in meat farms. Recent scientific knowledge in animal behaviour informs us that keeping any animal in extreme confinement, such as rabbits used for meat in intensive farms, has serious welfare concerns resulting in physical and psychological suffering. It is within this context that this thesis asks whether the concept of animal welfare in the caged rabbit meat industry is in effect an oxymoron. This thesis draws on work by Bekoff and Pierce’s ethological approach to support my critique of animal welfare practices in Australia’s rabbit meat industry. I also use Garner’s theory of incremental change in animal welfare reform, in which he argues for using current knowledge in animal welfare to push the boundaries of what is considered ‘unnecessary suffering’, as a social driver for a moral shift aimed at effecting law reform. To complement Garner’s political theory of incremental change I deploy Spira’s approach to advocacy, as practical tools for realising change.